Heat production and performance of broilers can be changed by inclusion of glycerin in their diet - Edna Teles dos Santos; Leilane Rocha Barros Dourado; Hidaliana Paumerik Aguiar Bastos; Regina Fialho de Sousa; João Batista Lopes; Leonardo Atta Farias; Francinete Alves de Sousa Moura; Daniel Biagiotti; Nilva Kazue Sakomura (Revista Científica de Produção Animal, 2020)
Glycerin has low heat increment and earlier studies on broilers evaluated its effects during the entire rearing period or in two phases at most. This study aimed to evaluate the effects of crude glycerin in diets of poultry on the performance and heat production of broiler chickens. For this, four evaluation phases (1-7, 8-21, 22-34, and 35-42 days of age) were established and 540 Cobb male broilers were distributed in a completely randomized design in six groups, each one with four replicates. The broilers were fed with diets containing 0 (control), 2.5, 5.0, 7.5, 10.0 and 12.5% glycerin. Feed consumption, weight gain, feed conversion ratio, and heat production were evaluated in each phase. The inclusion of up to 12.5% glycerin had a linear effect (P < 0.05), resulting in an improvement in feed conversion ratio, with no change in weight gain and feed consumption in the phase 1-7 days. There was no effect of the glycerin levels on the performance characteristics in the phases 8-21, 22-34, and 35-42 days of age. Some effect on heat production could be observed only in the phase 1-7 days of age (P<0.05), which was linear and decreasing. Glycerin can be added to the diets in up to 12.5% in all phases, not causing negative effects on the performance of broiler chickens. The addition of 12.5% glycerin reduced heat production in the phase 1-7 days of age.